Effect of biochar composition and paclobutrazol concentration on growth and yield of G1 Medians cultivar potato seeds in Jatinangor medium plain - Hamdani, Jajang Sauman; Putri, Zahira Salsabilla Idris; Sutari, Wawan (Kultivasi, 2024)
Potato seed production in the medium plain is necessary to avoid environmental damage and the limited area of potato seed production in the high plain. The effort to increase the production of G1 potato seeds on the medium plain is the evaluation of the biochar composition and concentration of paclobutrazol that can increase the production G1 potato seeds cv Medians in the medium plain of Jatinangor. The research was conducted from August to December 2022 at the Ciparanje Experimental Field. Jatinangor. Faculty of Agriculture. Universitas Padjadjaran. The experiment used a Factorial Randomized Block Design (RBD). The first factor was the biochar composition: m1 (100% compost), m2 (80% compost + 20% rice husk biochar), m3 (80% compost + 20% coconut shell biochar), and m4 (80% compost + 10% biochar husk rice + 10% coconut shell biochar). The second factor was the paclobutrazol concentration: p1 (without paclobutrazol), p2 (100 ppm paclobutrazol), and p3 (150 ppm paclobutrazol). The experimental results showed that there was no reaction effect of biochar compositions and paclobutrazol concentrations on the growth and yield of G1 potato seeds. The application of 80% compost + 20 % rice husk biochar gave significantly higher yields than treatment without biochar. The number of tubers was 6.29 knol per plant and the tuber weight was 66.80 g per plant. Application of 100 ppm paclobutrazol resulted in lower plant height, gave the number of tubers was 6.39 knol per plant, tuber weight per plant was 63.34 g higher than without paclobutrazol and produced more seed tubers with S class.